Regioselective lipase acylation as a useful tool for separation and selective protection of beta-D-Gal(1 -> 4)-D-GlcNAc and beta-D-Gal(1 -> 3)-D-GlcNAc disaccharides - B. La Ferla; L. Panza; L. Lay; G. Russo (Tetrahedron: Asymmetry, 2000)
Supported lipase from Candida antarctica (Chirazyme((R))) was employed for a regioselective protection of the 2-azido derivatives 1 and 2, synthetic equivalents of beta-(D)-Gal(1 ->3)-(D)-GlcNAc and beta-(D)-Gal(1->4)-(D-)GlcNAc (N-acetyl lactosamine), respectively. The selectivity of the enzyme towards 1 and 2 was also exploited for an easy separation of the mixture of the two compounds obtained from a straightforward synthetic approach. (C) 2000 Elsevier Science Ltd. All rights reserved.